THE RELEVANCE OF NURCHOLISH MADJID’S ISLAMIC POLITICAL THOUGHT ON DEMOCRACY TO THE POLITICAL ORIENTATION OF GENERATION Z WITHIN ISLAMIC STUDENT ORGANIZATIONS IN MEDAN CITY (Sophist: Jurnal Sosial Politik Kajian Islam dan Tafsir, 2026)
This study examines the relevance of Nurcholish Madjid’s Islamic political thought on democracy to the political orientation of Generation Z within Islamic student organizations in Medan City. The research employs a qualitative approach through field research supported by library research. Data were collected through in-depth interviews with members of the Himpunan Mahasiswa Islam (HMI), Pergerakan Mahasiswa Islam Indonesia (PMII), and Ikatan Mahasiswa Muhammadiyah (IMM), as well as documentation and literature review. Informants were selected using purposive sampling, while data were analyzed using the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The findings reveal that Nurcholish Madjid’s democratic principles such as deliberation (shura), justice, pluralism, openness, equality, and public participation remain highly relevant to the political orientation of Generation Z. Members of Islamic student organizations demonstrate democratic values through participatory decision-making, respect for diverse opinions, and active engagement in social and political issues. Furthermore, Generation Z tends to adopt a critical, rational, and issue-based political orientation rather than one centered solely on identity politics. Despite challenges posed by political polarization, digital misinformation, and declining public trust in political elites, Islamic student organizations continue to serve as strategic platforms for political education and leadership development. Therefore, Nurcholish Madjid’s democratic thought remains a significant moral and intellectual foundation for fostering a moderate, inclusive, democratic, and responsible political culture among Generation Z in contemporary Indonesia.